LITERASI DIGITAL DAN KEWIRAUSAHAAN: MEMPERSIAPKAN GENERASI MUDA MENGHADAPI TANTANGAN BISNIS DIGITAL - Felix, Antonius; Sutrisno, Julius; Bernanda, Devi Yurisca; Makarawung, Reynard J.N.; Kembau, Agung Stefanus; Hong, Kristy (Universitas Bunda Mulia, 2025)
The integration of digital literacy in secondary education is vital for fostering students' entrepreneurial skills. The Community Service Program (PKM)